Vloga kvantitativne senzorimetrije v rehabilitacijski medicini - Moharić, Metka (Rehabilitacija (Ljubljana), 2012)
Quantitative sensory testing is a term used to describe different forms of psychophysical testing of skin, mucosa or muscle tissues used for assessing sensory and painperception pathways. Quantitative sensory testing is able to capture and quantify stimulus-evoked negative and positive sensory phenomena. To yield useful results, quantitative sensory testing requires a cooperative subject and carefully standardized methods, including standardization of the stimulus parameters as well as the testing environment, instructions and evaluation methods. Over the past few decades, quantitative sensory testing has been most often used for the detection of sensory deficits and has played a significant role in laboratory and clinical neuropathic pain research. Its broader clinical acceptance is precluded by many concerns, especially lack of standards regarding methodology, although it provides valuable information about functional status of the thermo-nociceptive system.
Keywords: diagnostika; kvantitativna senzorimetrija; neurology; nevrologija; občutljivost; quantitative sensory testing; sensibility; termotest; thermotest; vibrametry; vibrometrija